DEVELOPMENT OF A CASH SYSTEM AND WEB-BASED ACCOUNTING INFORMATION SYSTEM AT PETAPAN PARK TOURIST ATTRACTION IN KLUNGKUNG REGENCY - Dwi Artawan, I Gusti Ngurah Adie; Pradnyana Yudha, Gusi Komang; Yusmarisa, Ni Luh Riska; Mareni, Ni Ketut; Arnawa, I Putu (Transpublika Publisher, 2024)
This study reveals that Petapan Park Tourism Object still relies on a manual system for financial data collection and operational activities, especially in ticket sales, parking, rides, and financial reporting. A descriptive research method was used to gather qualitative data through direct observation and interviews with the managers of Petapan Park Tourism Object. The results of this study led to the implementation of a cash system and a web-based accounting information system called FOS (Financial Operating System). FOS provides profit and loss statements and balance sheets as its final output with three main features: Transaction Menu, Financial Report Menu, and Master Data Menu. The cash system itself consists of Restaurant Sales Receipts, Recreation Sales Receipts, and Cash Disbursement Request Forms. A manual book is also provided to guide managers in using this system. The aim of this study is to enhance efficiency and accuracy in financial management at Petapan Park Tourism Object.